Anti-proliferative effect of pomegranate peel extracts on bovine peripheral blood mononuclear cells (PBMCs). Issue 10 (19th May 2021) - Mastrogiovanni, Fabio; Romani, Annalisa; Santi, Luca; Lacetera, Nicola; Bernini, Roberta
Abstract: Pomegranate peel extracts prepared in our laboratories from a waste of juice fruit processing were tested on bovine peripheral blood mononuclear cells to evaluate the effects on viability, oxidative stress and proliferation. The (3-[4, 5-dimethylthiazol-2-yl]-2, 5 diphenyl tetrazolium bromide) assay pointed out that the extracts were not cytotoxic at the tested concentrations (0.1, 1.0, and 10 µg/mL). A moderate protective effect against Reactive Oxygen Species production induced by hydrogen peroxide or lipopolysaccharide and a significant anti-proliferative activity against proliferation induced by concanavalin A were observed on cell lines treated with the extracts at 10 μg/mL. Based on these results, pomegranate peel extracts seem promising as feed supplement for dairy cattle, in particular around calving, when the animals are subjected to an increase of the metabolic activity, responsible for oxidative stress and diseases. However, in vivo studies are needed to investigate the stability of the extracts across the bovine gastrointestinal tract barrier. Graphical Abstract: